1974
DOI: 10.1073/pnas.71.9.3716
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Cost-of-Selection Concept

Abstract: It is shown for a continuous haploid model that the common standard assumptions usedin calculating the cost of gene substitution, namely, large constant population size and small constant selective value, are unnecessary. Population size may fluctuate during the course of substitution without affecting the calculated total cost. The selective intensity does not need to be small and constant to give the standard result for substitution cost. Diploid models with multiple alleles are analyzed and contrasted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…The fixation process is a conservative phenomenon. Flake et al [11] showed that the cost of substitution is associated with a potential energy function and Kimura [12] describes diffusion models to model the changes in gene frequencies in populations over generations. It is well known that diffusion equations are obtained by applying the principles of conservation of energy or mass to control volumes.…”
Section: Discussionmentioning
confidence: 99%
“…The fixation process is a conservative phenomenon. Flake et al [11] showed that the cost of substitution is associated with a potential energy function and Kimura [12] describes diffusion models to model the changes in gene frequencies in populations over generations. It is well known that diffusion equations are obtained by applying the principles of conservation of energy or mass to control volumes.…”
Section: Discussionmentioning
confidence: 99%
“…Selection comes at a cost in that some organisms must die before reproducing each generation for their genes to be selected against the wild-type allele, therefore causing a reduction in the overall population size. [28][29][30][31] A consequence of this cost is that the amount of selection that a population can withstand, without dropping to unsustainably low demographic levels, is limited. Haldane noted that for this reason, there is a limit to the number of traits that plant breeders are able to select at a given time, and that the pace at which evolution can be driven by natural selection is limited because of the cost of selection.…”
Section: Introductionmentioning
confidence: 99%
“…The Lenski experiment demonstrates how his bacteria must compete with each other in order to evolve to the selection pressure, starvation. In fact, differential reproductive fitness is simply a restatement of the law of conservation of energy, as shown by Flake and Grant in their paper An Analysis of the Cost of Selection Concept [9]. However, RMNS is not a conservative phenomenon.…”
Section: Discussionmentioning
confidence: 99%